Detection of human herpesvirus 6 (HHV-6) and human herpesvirus 7 (HHV-7) DNA in endocervical samples from a positive and negative HPV woman of Córdoba, Argentina. Issue 1 (17th July 2019) - Biganzoli, Patricia; Frutos, María Celia; Venezuela, Fernando; Mosmann, Jessica; Kiguen, Ana; Pavan, Jorge; Ferreyra, Leonardo; Cuffini, Cecilia
Abstract : Aims: The purpose of the present study was to elucidate the presence of human herpesvirus 6A (HHV-6A), HHV-6B and HHV-7 in samples of the uterine cervix through detection of viral DNA. We analysed normal tissues, samples with low-grade squamous intraepithelial lesions (LSILs) and high-grade squamous intraepithelial lesions (HSILs). We correlated the presence of HHV-6 and HHV-7 with the finding of human papillomavirus (HPV) in mucosal samples. Methods: Cervical samples were examined and grouped as follows: group 1 (n=29), normal cytology; group 2 (n=61), samples with LSIL; group 3 (n=35), samples with HSIL. Molecular biology examinations were performed in all samples to detect HHV-6, HHV-7 and HPV DNA and to typify HHV-6 species. Results: Group 1: normal cytology and HPV (−): HHV-6: 6.8% (2/29), HHV-7: 79.3% (23/29); group 2: LSIL and HPV (−): HHV-6: 93.1% (27/29), HHV-7: 96.5% (28/29); LSIL and HPV (+): HHV-6: 0% (0/32), HHV-7: 90.6% (29/32); group 3: HSIL and HPV (−): HHV-6: 20% (2/10), HHV-7: 70% (7/10); HSIL HPV (+): HHV-6: 12% (3/25), HHV-7: 68% (17/25). HHV-6A DNA was not detected in any samples. Conclusions: (1) Both HHV-6 and HHV-7 infect the mucosal cells of the cervix with higher prevalence of HHV-7. (2) The higher prevalence of HHV-6 in LSIL HPV (−) samples compared with those with normal cytology indicates that it constitutes a possible risk factor for atypia production. (3) The presence of HHV-7 in all samples questions its role in the production of atypia. (4) The finding of HHV-6 and HHV-7 suggests that the cervical mucosa is a possible transmission pathway for these viruses.